2019
DOI: 10.1001/jamaoncol.2018.6720
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Options for Neuroendocrine Tumors

Abstract: IMPORTANCE Multiple therapies are currently available for patients with neuroendocrine tumors (NETs), yet many therapies have not been compared head-to-head within randomized clinical trials (RCTs). OBJECTIVE To assess the relative safety and efficacy of therapies for NETs. DATA SOURCES PubMed, Embase, the Cochrane Central Register of Controlled Trials, trial registries, meeting abstracts, and reference lists from January 1, 1947, to March 2, 2018, were searched. Key search terms included neuroendocrine tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 68 publications
0
44
1
2
Order By: Relevance
“…Among the therapies showing good efficacy, SSA in combination with 177 Lu-dototate showed a better profile in term of toxicity in respect to Everolimus (94% AE, 41% grade 3-4). Interferon and SSA caused AE in 21% of the patient and a small percentage of a grade 3-4 (3%) while SSA alone caused AE in 69.8% of the cases and 20.9% of AE of grades 3-4 (105). A metaanalysis of individual patient data showed that a 2-fold increase in Everolimus Cmin delayed NET disease progression with improved tumor size reduction.…”
Section: Meta-analysismentioning
confidence: 99%
“…Among the therapies showing good efficacy, SSA in combination with 177 Lu-dototate showed a better profile in term of toxicity in respect to Everolimus (94% AE, 41% grade 3-4). Interferon and SSA caused AE in 21% of the patient and a small percentage of a grade 3-4 (3%) while SSA alone caused AE in 69.8% of the cases and 20.9% of AE of grades 3-4 (105). A metaanalysis of individual patient data showed that a 2-fold increase in Everolimus Cmin delayed NET disease progression with improved tumor size reduction.…”
Section: Meta-analysismentioning
confidence: 99%
“…Furthermore, the addition of SSAs would appear to promote a synergistic effect, increasing the DCR in this patient subgroup. A recently published network meta-analysis supports this hypothesis of the additional effect of the SSA combination with other therapies (33).…”
Section: Summary Of Main Findingsmentioning
confidence: 78%
“…In the randomized clinical trials (RCT) of neuroendocrine tumors, 22 different therapy strategies were compared, stating that there are a number of effective therapies with different safety profiles available to patients, suggesting an overall superiority of combination therapies [62]. For patients with advanced NETs as a best second-and third-line treatment, respectively, to progression-free survival (PFS), PRRT, SSA + bevacizumab, and SSA + interferonalfa should be considered [63].…”
Section: The Treatment Of Neuroendocrine Neoplasmsmentioning
confidence: 99%